Complications and Management of Endoscopic Spinal Surgery - Ju, Chang Il; Lee, Seung Myung (Neurospine, 2023)
In the past, the use of endoscopic spine surgery was limited to intervertebral discectomy; however, it has recently become possible to treat various spinal degenerative diseases, such as spinal stenosis and foraminal stenosis, and the treatment range has also expanded from the lumbar spine to the cervical and thoracic regions. However, as endoscopic spine surgery develops and its indications widen, more diverse and advanced surgical techniques are being introduced, and the complications of endoscopic spine surgery are also increasing accordingly. We searched the PubMed/MEDLINE databases to identify articles on endoscopic spinal surgery, and key words were set as “endoscopic spinal surgery,” “endoscopic cervical foramoinotomy,” “PECD,” “percutaneous transforaminal discectomy,” “percutaneous endoscopic interlaminar discectomy,” “PELD,” “PETD,” “PEID,” “YESS” and “TESSYS.” We analyzed the evidence level and classified the prescribed complications according to the literature. Endoscopic lumbar surgery was divided into full endoscopic interlaminar and transforaminal approaches and a unilateral biportal approach. We performed a comprehensive review of available literature on complications of endoscopic spinal surgery. This study particularly focused on the prevention of complications. Regardless of the surgical methods, the most common complications related to endoscopic spinal surgery include dural tears and perioperative hematoma. transient dysesthesia, nerve root injury and recurrence. However, Endoscopic spinal surgery, including full endoscopic transforaminal and interlaminar and unilateral biportal approaches, is a safe and effective a treatment for lumbar as well as cervical and thoracic spinal diseases such as disc herniation, lumbar spinal stenosis, foraminal stenosis and recurrent disc herniation.